2021
DOI: 10.26434/chemrxiv.10316819.v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Thermodynamic Way of Assessing Reversible Metal Hydride Volume Expansion: Getting a Grip on Metal Hydride Formation Overpotential

Abstract: <p>The relative volume expansion of reversible metal hydride crystals upon formation is determined by means of the van’t Hoff reaction entropy and STP ideal gas parameters, the development of this approach leads to a general method for calculating metal hydride single-crystal density. These results allow highlighting the pressure requirement to hydride phase formation, shown by the example of Ti-NaAlH<sub>4</sub>.</p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is reasonable to relate the effects caused by KH-doping with the next stable mixed alanate K 2 NaAlH 6 , 9 as KNa 2 AlH 6 is instable. 11,12 Its density is calculated by the entropy method, 10 on basis of the data of SØRBY et al, 13 as shown in equations 3a to 3c; the required NaH and Al densities base on Römpp's chemistry lexicon, 14,15 those of KH on data provided by American Elements. The doping effect in the sorbent is indirectly determined via gas phase thermodynamics: starting from a gas volume at IUPAC standard temperature and pressure (STP), introducing the sorbent phase entails hydrogen absorption respective hydride formation.…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to relate the effects caused by KH-doping with the next stable mixed alanate K 2 NaAlH 6 , 9 as KNa 2 AlH 6 is instable. 11,12 Its density is calculated by the entropy method, 10 on basis of the data of SØRBY et al, 13 as shown in equations 3a to 3c; the required NaH and Al densities base on Römpp's chemistry lexicon, 14,15 those of KH on data provided by American Elements. The doping effect in the sorbent is indirectly determined via gas phase thermodynamics: starting from a gas volume at IUPAC standard temperature and pressure (STP), introducing the sorbent phase entails hydrogen absorption respective hydride formation.…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to relate the effects caused by KH-doping with the next stable mixed alanate K 2 NaAlH 6 , 9 as KNa 2 AlH 6 is instable. 11,12 Its density is calculated by the entropy method, 10 on basis of the data of SØRBY et al, 13 as shown in equations 3a to 3c; the required NaH and Al densities base on Römpp's chemistry lexicon, 14,15 those of KH on data provided by American Elements. The doping effect in the sorbent is indirectly determined via gas phase thermodynamics: starting from a gas volume at IUPAC standard temperature and pressure (STP), introducing the sorbent phase entails hydrogen absorption respective hydride formation.…”
Section: Resultsmentioning
confidence: 99%
“…A work primarily concerned with metal volume expansion upon hydride formation shows the conditional threshold pressure to hydride phase formation being given by the relation of equation 1, derived by means of the ideal gas law for the exemplary problem of [AlH 4 ]-formation in Ti-NaAlH 4 . 10 p > 4005 V m, NaAlH4 bar cm 3 (mol…”
Section: Methodical Approachmentioning
confidence: 99%
See 1 more Smart Citation